Synergy or conflict? political-administrative interactions in local governance at Kibaha Town Council, Tanzania - Kasanga, Philomena; Massoi, Lucy Willy (2026)
This study examines the impact of political-administrative interactions on local governance in Tanzania, using Kibaha Town Council as a case study. Drawing on the Political-Administrative Dichotomy (PAD) and the Classical Model of Public Administration, the study explores how these interactions influence decision-making, policy implementation, and service delivery at the local level. Using a case study design and a mixed-methods approach, data were collected from 52 respondents, including elected officials (Members of Parliament, Councilors, and Town Chairpersons) and appointed officials (District Commissioner and Town Director). A total of 52 respondents were selected using purposive and simple random sampling techniques from a population size of 91 employee of Kibaha Town Council. Qualitative data from interviews were analyzed thematically, while quantitative data were processed using descriptive and inferential statistical methods. Findings reveal that 91.2% of respondents perceive political administrative interactions as positively impacting governance, particularly in policy formulation, law-making, and development administration. However, challenges such as role ambiguity and conflicts between politicians and administrators remain significant obstacles to effective governance. This study concludes that addressing these challenges through clearer role definitions, improved communication channels, and enhanced monitoring and evaluation (M&E) mechanisms can strengthen governance structures. While the study focuses on Kibaha Town Council, its findings contribute to the broader understanding of political- administrative interactions in Tanzania’s local governance system. This research recommends the establishment of a well-defined legislative framework to streamline governance operations, ensuring that political and administrative roles complement rather than conflict with each other. Furthermore, standardized guidelines across local government authorities (LGAs) would promote consistency, collaboration and institutional efficiency.